2020
DOI: 10.2174/1871530319666190614121738
|View full text |Cite
|
Sign up to set email alerts
|

The Association between HbA1c Levels, Olfactory Memory and Cognition in Normal, Pre-Diabetic and Diabetic Persons

Abstract: Background and Aim: Recent data have shown that olfactory dysfunction is strongly related to Alzheimer’s Disease (AD) that is often preceded by olfactory deficits suggesting that olfactory dysfunction might represent an early indicator of future cognitive in prediabetes. Methods: We have applied to a group of normal (n=15), prediabetic (n=16) and type 2 diabetic outpatients (n=15) olfactory testing, 1.5-T MRI scanner and detailed cognitive evaluation including the standard Mini-Mental State Examination (MMSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…Of note, a recent study involving type 2 diabetic patients demonstrated not only increased OI in this population compared to controls but also diminished abilities in specific cognitive tests. Besides, once again, they found a strong association between OI and specific memory impairment in this population (Yulug et al, 2019). As for smoking, which is known to interfere with olfactory performance, the effect is equivocal or weak and mostly seen in long-standing heavy smokers (Mackay-Sim et al, 2006).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Of note, a recent study involving type 2 diabetic patients demonstrated not only increased OI in this population compared to controls but also diminished abilities in specific cognitive tests. Besides, once again, they found a strong association between OI and specific memory impairment in this population (Yulug et al, 2019). As for smoking, which is known to interfere with olfactory performance, the effect is equivocal or weak and mostly seen in long-standing heavy smokers (Mackay-Sim et al, 2006).…”
Section: Introductionmentioning
confidence: 66%
“…Indeed, a recent study found that older adults with high insulin resistance (quantified by the HOMA-IR test) had an approximately 2-fold increased odds of OI compared with subjects with low insulin resistance (Min and Min, 2018). This could explain, at least in part, the independent association found between type 2 diabetes mellitus (in which insulin resistance represents the key mechanism) and OI (Gopinath et al, 2012;Gouveri et al, 2014;Yulug et al, 2019). OI in type 2 diabetes mellitus might also be due to microvascular injury since OI was mainly found in diabetic patients already suffering from the microvascular complications of this disease (Gouveri et al, 2014).…”
Section: Reflection Of General Poor Healthmentioning
confidence: 99%
“…Autoimmune diseases have long been associated with smell loss 1709,1710 . Specifically, patients with Sjögren syndrome and SLE have been found to commonly exhibit olfactory deficits.…”
Section: Managementmentioning
confidence: 99%
“…1708 Treatment of OD related to autoimmune diseases Autoimmune diseases have long been associated with smell loss. 1709,1710 Specifically, patients with Sjögren syndrome and SLE have been found to commonly exhibit olfactory deficits. Schonfeld et al 1711 reported that the odor threshold and odor discrimination scores decreased in patients with SLE, and that OD correlated with disease severity and CNS involvement.…”
Section: Treatment Of Od Related To Endocrine and Metabolic Diseasesmentioning
confidence: 99%
“…Recent studies have confirmed that there was an interplay between diabetes mellitus, olfaction, and dysfunction of the central nervous system. In a prospective study of 15 normal, 16 prediabetic, and 15 T2DM subjects, a strong association between olfactory dysfunction and specific memory impairment was observed among subjects with prediabetes and diabetes [ 39 ]. Moreover, among 151 older Japanese T2DM subjects, those with olfactory dysfunction at baseline developed dementia more frequently after 3 years than those without smell impairment [ 40 ].…”
Section: Potential Mechanisms Associating Diabetes With Olfactory Dysfunctionmentioning
confidence: 99%